The sparing phenomenon of cutaneous amyloidosis - Zhou, Hui-Wen; Tan, Cheng (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2021)
The sparing phenomenon (SP) denotes a particular skin disease which spares an anatomic site or an area affected by other skin disorders [1]. SP occurs in miscellaneous skin conditions such as herpes zoster, drug eruptions, alopecia areata and so on. For the first time, both the nipple-areola complex and the depigmented skin in vitiligo were found to be spared in cutaneous amyloidosis.